Improving Video-on-Demand Performance by Multi-channel/Multicast Approach in Wireless Networks - Kalan, Reza Shokri (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: Video on-demand (VoD) services and applications have become popular in wireless networks. VoD refers to requesting video which is stored on remote media servers. Many commercial products (e.g. PPLive and PPStream) are developed to support VoD applications. Two popular approaches in VoD area are peer-to-peer (P2P) and clientserver models. In a network (WAN, LAN, WWAN, or WLAN) when a client initiates a video request, it can stream the video from the servers on the network or from peer clients. Many networks use P2P technology to improve the VoD performance. In P2P models, users store watched videos in their own local storages and can distribute them through the network to other peers when other users want to watch the same video. In this manner clients can download video from suitable neighbors. There are two ways for accessing a video stream: (a) over wired networks, (b) over wireless networks. Video on-demand streaming has been applied in wired networks with success. However, it remains a challenging task in wireless networks due to bandwidth problems and the effect of wireless interference and client mobility. This study aims at improving VoD performance in wireless networks based on multicasting and patching in clients. The simulation results show that the suggested methods improve VoD performance. Keywords: Video on demand, Wireless networks, Cellular networks, Frequency band, and Buffer management. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Video on-demand (VoD) hizmetleri ve uygulamaları kablosuz aglarda popüler olarak kullanılmaktadır. VoD uzaktan medya sunucuları üzerinde depolanan bir videoyu talep etmek anlamına gelir. VoD alanında iki popüler yaklasım peer-to-peer (P2P) ve istemcisunucu modelleridir. WAN,LAN,WWAN,veya WLAN türü bir agda bir istemci bir video talep ettiginde, ilgili videonun bölümlerini uzak sunuculardan veya “komsulardan” indirebilir. P2P modelinde kullanıcılar izledikleri videoları kendi yerel bellekerinde tutarak, aynı ag içinde baska istemcilerden gelecek istekleri cevaplamak üzere devreye girebilirler. Böylece bir istemci, izlemek istedigi videonun bölümlerini “komsusundan” indirebilir. Bir videoyu kablolu veya kablosuz aglardan indirmek mümkündür. Kablolu aglar için bu konuda yeterli çalısma yapılmıstır. Ancak, kablosuz aglarda baglantı hızı, kullanıcının hareketliligi ve girisini sorunları nedeniyle etkin video transferi halen önemli bir arastırma konusudur. Bu çalısmada, kablosuz aglarda video transfer performansını arttırmak içın çoklu iletim (multicasting) ve yamalama (patching) yöntemleri önerilmis ve modellenerek simülasyonu gerçeklestirilmistir. Bulunan sonuçlar, önerilen yöntemlerin performansı arttırabildigini göstermektedir. Anahtar Kelimeler: Talep edilen video, Kablosuz aglar, Hücresel aglar, Frekans bandı ve Tampon bellek yönetimi.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assoc. Prof. Dr. Işık Aybay.
Keywords: Computer Engineering; Multimedia Systems; Video on Demand - Wireless Networks - Cellular Networks - Frequency Band and Buffer Management